Development Of Community Research & Information System Application For Web-Based National University Lecturers: Development Of Community Research & Information System Application For Web-Based National University Lecturers - Adnan Wahab; Iwan Wahyudin; Nur hayati (Jurnal Mantik, 2020)
(LPPM) National University Research and Community Service Institute in general is research and community service aimed at improving the quality of human resources by conducting targeted research so that research results can be used according to community demands. In addition, this institution also facilitates and implements research results as a service work that is beneficial to the community. During this time the administrative process in reporting the results of research carried out by accessing the website contained in the url http://sippm.unas.ac.id/, but the existing website is no longer managed and used. Therefore it will be made Research & Community Service Applications for Web-Based National University Lecturers, where this application is the development of the previous website. With this system, it is expected to facilitate lecturers in conducting administrative processes related to reporting research results. The results of the research that have been carried out, is the implementation of the application using the PHP MySQL programming language, and also using the SDLC Waterfall Method in its development.